LEGAL STATUS OF DOWRIES PROVISION BY THIRD PARTIES - Kusmayanti, Hazar; Djanuardi, Djanuardi; Hadiyanti, Nurmeida; Yuanitasari, Deviana (Faculty of Law, Parahyangan Catholic University, 2019)
This article discusses the issue of the legal validity of marriage contract in the case dowry is paid by a third party. Legal analysis will be performed on the legal principles and regulations found in The Law Number 1 Year 1974 on Marriage, The Compilation of Islamic Law and sources in Islamic Law . One important finding is does not forbid the payment of dowry by a third party and that this practice does not affect the validity of the marriage contract.